2007
DOI: 10.1002/anie.200605095
|View full text |Cite
|
Sign up to set email alerts
|

Cu2(OTf)2‐Catalyzed and Microwave‐Controlled Preparation of Tetrazoles from Nitriles and Organic Azides under Mild, Safe Conditions

Abstract: In connection with a project aimed at preparing new series of diketotetrazoles (see compound 1 in Scheme 1, for which two representative tautomers are shown) and pharmacophorrelated quinolinocarbonyltetrazoles, as further candidates for HIV-1 integrase inhibitors, [1] we sought a rapid entry into the synthesis of tetrazole esters 2 and/or 5-acetyltetrazoles 3 (Scheme 1). Formation of tetrazole rings by cycloaddition between nitriles and organic azides is in principle the most direct method, [2] but it usually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
55
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(55 citation statements)
references
References 45 publications
0
55
0
Order By: Relevance
“…For the reluctant secondary azide 188, an AZT derivative, however, it was found that heating at 80°C under microwave irradiation conditions for a few hours was able to force the reaction to proceed. [127] Scheme 68.…”
Section: Cycloadditions Of Azidesmentioning
confidence: 99%
“…For the reluctant secondary azide 188, an AZT derivative, however, it was found that heating at 80°C under microwave irradiation conditions for a few hours was able to force the reaction to proceed. [127] Scheme 68.…”
Section: Cycloadditions Of Azidesmentioning
confidence: 99%
“…[71][72][73][74][75][76][77][78][79][80] The range of metal salts applied to the preparation of the tetrazole-containing coordination compounds constantly grows. However their efficiency is variable.…”
Section: Scheme 11mentioning
confidence: 99%
“…(B) The title reagent was used to prepare an acetylenic ester that served as an early stage intermediate in the first asymmetric total synthesis of (-)-platensimycin reported by Nicolaou and co-workers. 6 (D) Nájera and co-workers reported the one-step synthesis of various chiral cyanocarbonates from a range of aldehydes using the title reagent in the presence of chiral bifunctional catalysts such as (R)-or (S)-BINOLAM-AlCl. 12,13 It is believed that the catalytic cycle involves enantioselective hydrocyanation promoted by BINOLAMAlCl, followed by the turnover-limiting O-alkoxycarbonylation step.…”
Section: Introductionmentioning
confidence: 99%